Effect of sulphur dioxide exposure on human chromosomes - Yadav, J.S.; Kaushik, V.K. (Mutation Research, 1996)
The genotoxic effects of an average concentration of 41.7 mg/m 3 of SO 2 exposure on 42 workers of a fertilizer factory were investigated. Mitotic index (MI), chromosomal aberrations (CAs), sister-chromatid exchanges (SCEs) and satellite associations (SA) were observed. In SO 2-exposed workers, a higher mitotic index (7.09) was recorded in comparison to controls (4.34). The MI, however, declined with duration of exposure. Satellite associations showed a two-fold increase (17.1) as compared to controls (8.11). Among chromosomes, D-G group associations were the highest (7.43%), while 3D type associations were the lowest (0.4%). There was a significant difference ( p < 0.05) in the mean frequency of CAs per cell in the exposed workers (3.262%) and the controls (0.833%). The mean frequency of SCEs per cell increased from 3.32 ± 0.1 in controls to 7.72 ± 0.19 in the exposed group. The difference was significant ( p < 0.05). In smokers, alcoholics and smoker-alcoholics, the frequency of CAs and SCEs per cell was significantly higher than the non-smokers and non-alcoholics, both in the controls and the SO 2-exposed workers and showed a correlation with the duration of exposure. SO 2 is therefore a clastogenic and genotoxic agent for which necessary precautions must be taken.